Distribution pattern and sequential sampling plan for spotted pod borer, Maruca vitrata (Fabricius) (Lepidoptera: Crambidae) on pigeon pea, Cajanus cajan L. Issue 1 (2nd January 2016) - Sujithra, M.; Chander, Subhash
Abstract : Spatial distribution of legume pod borer, Maruca vitrata (Fabricius) (Lepidoptera: Crambidae) on Pusa 992 pigeon pea cultivar during kharif (rainy season) 2011 and 2012 was analyzed through Taylor's power law (TPL) and Iwao's mean crowding (IMC) regression. M. vitrata exhibited an aggregated distribution pattern on the crop. The pooled data for the two years fitted well to the TPL ( a = 1.05, b = 1.19, R 2 = 0.967) and the IMC (α = −0.17, β = 1.124, R 2 = 0.99). The optimal sample sizes with the TPL parameters increased with an increased precision level. Based on the TPL parameters, the decision lines of sequential sampling for M. vitrata were determined to be d = 3 n ± 2.5√ n . The sequential sampling plan would economize decision-making for an effective management of M. vitrata .